My Theatre Life (Wesleyan University Press, 1979)
Born in Copenhagen in the early nineteenth-century and trained by his father, French ballet master, Antoine Bournonville, August Bournonville was an iconoic dance master and principal choreography of the Royal Danish Ballet with his incorporation of French Romanticism in his ballet choreography. Known for detailed, quick footwork and delicate arm and torso contrast, Bournonville's style of dance became known as the Bournonville Method, today considered the unfiltered 19th century technique of the French school of classical dance. Over a century since his death, Bournonville's influence remains seen on the Danish and greater European stage, imported to theatre classes and stages across the world.